As orientações para o uso dos sites nos livros didáticos da coleção História Global - Gomes, Eloisa Maria Godinho (2020)
The objective of this dissertation was to analyze the orientations present in a high school history didactic collection approved by PNLD 2018, for the use of sites in history teaching. Thus, the objectives outlined for this work were: to develop the debate about the research with textbooks and new technologies, especially the sites; to contextualize and analyze the National Textbook Program, focusing on the evaluation criteria related to new educational technologies; to choose one of the History collections for High School, approved by PNLD 2018; to locate and identify the sites present in the chosen didactic collection; to categorize the sites according to their general characteristics, that is, domain, content. The didactic collection analyzed was Global History by Gilberto Cotrim, which was the second most adopted collection in PNLD 2018. The research was due in three stages: the first, of inventory of the empirical material, the choice of the collection to be analyzed; the second, of analysis and categorization of the chosen material; the last stage consisted in the analysis of the empirical material. Thus, this study used some procedures of content analysis, from Bardin (2011) and Franco (2003). We took as theoretical reference the understanding of textbooks as a complex object with different functions according to Choppin (2004).